2021
DOI: 10.2147/dmso.s311274
|View full text |Cite
|
Sign up to set email alerts
|

Use of Eye Care Service and Associated Factors Among Adult Diabetic Patients Attending at Diabetic Clinics in Two Referral Hospitals, Northeast Ethiopia

Abstract: The objective of this study was to determine the proportion of use of eye care service and associated factors among adult diabetic patients attending diabetic clinics in two referral hospitals, Northeast Ethiopia, 2020. Methods: A hospital-based cross-sectional study was carried out with a sample size of 546 at Dessie and Debre-Birhan Comprehensive Specialized Hospitals from July 06 to August 14/2020. Systematic random sampling with a sampling fraction of 2 was employed to select study participants at outpatie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…The included articles were published between 2007 and 2022. From the included articles 3 studies are from Ethiopia [ [34] , [35] , [36] ], 2 are from Nigeria [ 23 , 37 ] and the remaining are from South Africa, Kenya, Ghana and Tanzania [ [38] , [39] , [40] , [41] ]. All the studies published in peer-reviewed journals ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The included articles were published between 2007 and 2022. From the included articles 3 studies are from Ethiopia [ [34] , [35] , [36] ], 2 are from Nigeria [ 23 , 37 ] and the remaining are from South Africa, Kenya, Ghana and Tanzania [ [38] , [39] , [40] , [41] ]. All the studies published in peer-reviewed journals ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, studies conducted in African countries (e.g. a study in South Africa (Akuffo et al, 2020), and Ethiopia (Ahmed et al, 2021) reported that the proportion of eye checkup services utilization in adult diabetics was 49% and found 31.5%, respectively. Ethiopia remains one of the top ve African diabetic countries (IDF, 2017), and the national prevalence of DR among adult diabetics was reported to be 34.1% (MERSHA et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, joint guidelines set by authority organizations recommend annual screenings for patients with diabetes [6,7]. However, the conditions of the normative management of regular fundus examinations among patients with diabetes are not satisfactory in many countries [8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have reported low adherence rates to annual fundus exams among the population with diagnosed diabetes to date [8][9][10][11][12][13][14][15]. Multiple factors have been considered to impacts on the poorer adherence to regular screenings in the population with diabetes, including racial disparities, coexistent diseases, educational level and insurance coverage [8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation